Implementasi Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perdesaan Di Kecamatan Banggae Timur Kabupaten Majene - . Safriansyah (PUBLICA, 2012)
PNPM is one program to accelerate poverty reduction in an integrated and sustainable. The purpose of this study is to investigate the process of implementation of PNPM Mandiri in Rural Eastern District of Banggae Majene and to identify the factors that influence it. The method used is deductive qualitative descriptive analysis method. Results reveal that the implementation of PNPM Rural in District East Banggae Majene has been implemented in accordance with the procedures set out in the process, although influenced by communication, resources, attitudes executor, and organizational structure. Communication factors, resources and organizational structure are factors that support the implementation of the program, while the attitude of factors, including the factors that inhibit the implementation of the program. However, the factors that hamper can be controlled in accordance with established procedures.